Selective flowers to attract and enhance Telenomus laeviceps (Hymenoptera: Scelionidae): a released biocontrol agent of Mamestra brassicae (Lepidoptera: Noctuidae). Issue 2 (10th May 2018) - Barloggio, G.; Tamm, L.; Nagel, P.; Luka, H.
Abstract: The importance of the right food source for the survival and reproduction of certain insect species is well documented. In the case of biocontrol agents, this is even more important in order to reach a high predation or parasitation performance. The egg parasitoid Telenomus laeviceps (Förster, 1861) (Hymenoptera: Scelionidae) is a promising candidate for mass release as a biological control agent of the cabbage moth Mamestra brassicae (Linnaeus, 1758) (Lepidoptera: Noctuidae). However, adult T. laeviceps need a sugar-rich food source to increase their parasitation performance and produce a good amount of female offspring. Released biocontrol agents were shown to benefit from conservation biocontrol, which includes the provision of selected flowers as nectar resources for beneficial insects. In Switzerland, Centaurea cyanus L. (Asteraceae), Fagopyrum esculentum Moench (Polygonaceae) and Vicia sativa L. (Fabaceae) are successfully implemented in the field to attract and promote natural enemies of different cabbage pests. In this study, we investigated the potential of these selected flowers to attract and promote T. laeviceps under laboratory conditions. In Y-tube olfactometer experiments, we first tested whether the three nectar providing plant species are attractive to T. laeviceps . Furthermore, we assessed their effects on survival and parasitation performance of adult T. laeviceps . We found that flowers of F. esculentum and C. cyanus were attractive in contrast to V. sativa. Also fecundity and the number of female offspring produced were higher for females kept on F. esculentum and C. cyanus than on V. sativa. In contrast, survival was similar on all treatments. Our findings present a further key step towards the implementation of T. laeviceps as a biocontrol agent.